FOCAL MECHANISM OF THE LITHUANIAN EARTHQUAKE OF BASED ON WAVEFORM INVERSION - Malytskyy, D.; Ņikuļins, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The aim: Determination of focal mechanism of Lithuanian earthquake of 12.06.15 (t0 = 08:18:26.4; 55.52° N, 21.40° E; hs = 0.9 км.; ML = 2.6) by waveform inversion using direct waves and a limited number of stations. Method: Matrix method is used for modelling of seismic wave propagation in the medium modelled as horizontally layered heterogeneous elastic structure. There were obtained the relations of displacement waves on the free surface that were used for seismic tensor determination using only direct P- and S- waves. Determination of seismic tensor and the focal mechanism on the base of developed method for a point source is described. Thus, based on forward modeling, numerical techniques are developed for the inversion of observed waveforms for the components of moment tensor. Results: In the paper, a method is presented for the focal mechanism determination of Lithuanian earthquake of 12.06.15 (ML = 2.6) by waveform inversion using limited number of stations. The focal mechanism is determined using the data from two stations: PABE, SLIТ and from three stations: PABE, MTSE, SLIТ. These seismic stations are the part of BAVSEN (BalticVirtualSeismicNetwork).Scientific novelty: 1. In the paper, a method is presented for moment tensor inversion for the focal mechanism determination of events with a low seismicity. The East Baltic region (EBR) is the region with low seismicity. 2. The focal mechanism is determined using the data from a limited number of stations. Practical significance: The results of focal mechanism determination can be used to study seismicity for regions with a low seismicity using a limited number of stations.